2017
DOI: 10.1063/1.4976892
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between safety culture dimensions and safety performance of construction projects through partial least square method

Abstract: Abstract. Based on the data, 32% of accidental cases in Indonesia occurs on constructional sectors. It is supported by the data from Public Work and Housing Department that 27.43% of the implementation level of Safety Management System policy at construction companies in Indonesia remains unsafe categories. Moreover, there are dimensions of occupational safety culture formed including leadership, behavior, strategy, policy, process, people, safety cost, value and contract system. The aim of this study is to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In order to determine the coefficients of the equations, a factor analysis was conducted using the SPSS program. Using factor analysis is an effective method for reducing the data's complexity by detecting any possible underlying patterns or constructions (Chen, 2022;Latief et al, 2017). To confirm the correctness and dependability of the data, the researchers employed the Kaiser-Meyer-Olkin (KMO) method to test the sample's adequacy and the Cronbach's alpha model to evaluate the study's reliability.…”
Section: Fig 2 Respondent Demographic Statisticsmentioning
confidence: 99%
“…In order to determine the coefficients of the equations, a factor analysis was conducted using the SPSS program. Using factor analysis is an effective method for reducing the data's complexity by detecting any possible underlying patterns or constructions (Chen, 2022;Latief et al, 2017). To confirm the correctness and dependability of the data, the researchers employed the Kaiser-Meyer-Olkin (KMO) method to test the sample's adequacy and the Cronbach's alpha model to evaluate the study's reliability.…”
Section: Fig 2 Respondent Demographic Statisticsmentioning
confidence: 99%
“…According to Latief et al, safety-related cultural characteristics impact safety behavior, processes, systems, and performance [16]. A study by Musonda et al found that a favorable culture contributes to enhanced occupational health and safety performance [17].…”
Section: Introductionmentioning
confidence: 99%